The role of corporate communication pt Angkasa Pura II (Persero) in communication of code of conduct (business ethics and work ethics) to employees to build anti-corruption attitude - Diah Wardhani; Nindyta Aisyah; Bangko, Suratani; Fitrie Handayani; Trisetio, Yusup; Kharisma, Alie Pradana; Darmawan, Iswan (Technium Social Sciences Journal, 2023)
The problem of corruption in Indonesia is still not completely resolved, even though there have been so many efforts to resolve it. Indonesia is even currently in the order of the most corrupt countries among the G 20 countries. Indonesia has a score of 37 on a scale of 0 -100, which is starting to be corrupt ( 0 ) and very clean. State losses due to corruption cases in semester 1 of 2021, reached Rp 26.83 trillion, an increase of 47.63% compared to the previous year. Efforts made by many organizations/companies to build an anti-corruption attitude continue to be made. One of them is PT Angkasa Pura II (Persero) which implements a Code of Conduct (Business Ethics and Work Ethics) for both internal and external public. Corporate Communications Division, AP II Jakarta, is one of the parties that communicates Code of Conduct to the internal public, in order to build an anti-corruption attitude for all employees. The purpose of this study was to find out the role of AP II’s Corporate Communication Division in communicating Code of Conduct to employees to build an anti-corruption attitude. The concept used is organizational communication, internal communication, corporate communications, code of conduct, business ethics, work ethics, employee, and anti-corruption attitude. The method of research are post positivism paradigm and descriptive method with a qualitative approach. Informants interviewed were Corporate Secretary, Corporate Communication Division and several employees who felt the communication process. The results show that the Corporate Communications Division collaborates with the Human Capital Policy Unit, and the Airport Learning Center in communicating the Code of Conduct to the internal public. The role of Corporate Communication Division is to carry out communication functions throughout the internal public, the Human Capital Unit translate the Code of Conduct in its implementation on resources, and the Airport Learning Center Unit uses a mobile learning application to deliver materials or Code of Conduct modules, which are downloaded by all personnel of Angkasa Pura II.